'New' direct oral anticoagulants in the perioperative setting - Breuer, Georg; Weiss, Dominik R.; Ringwald, Jürgen (Current Opinion in Anaesthesiology, 2014)
Out of the anesthetist's perspective, some uncertainties remain with the perioperative management of the so-called NOACs. This review emphasizes on the question of bleeding and thromboembolic risk as well as the management of bleedings and the discontinuing intervals in the context of regional anesthesia.Managing patients with NOAC therapy, an interdisciplinary approach and consent with surgeons and specialist in hemostaseology has to be found. For severe and lifethreatening bleeding there are specific antidotes in development; however, until clinical provement is not yet finished the application of four-factor prothrombin complex concentrate may be the most promising approach.NOACs like dabigatran etexilate, rivaroxaban, apixaban and edoxaban are effective alternatives to warfarin in primary and secondary prophylaxis of thromboembolic conditions. In the perioperative setting, some uncertainties and evidence gaps remain in estimating the bleeding risks associated with surgical procedures, emergency trauma and neuroaxial anesthesia. A discontinuation of NOACs should be at least 1 day before elective operation. Renal and liver impairment, older age, or co-medications could afford longer intervals. As no specific reversal agents are yet available for life-threatening bleeding or emergency surgery; nonspecific prohemostatic therapies are mainly recommended. Oral charcoal, application of tranexamic acid or hemodialysis could bring additional benefit depending on the individual NOAC. Practitioners need to be aware that NOACs can interfere in different pathways with the measurement of common hemostasis parameters. Estimating the bleeding risks and reversal strategies requires careful evaluation also in the light of a potential risk of thromboembolic complications. In difference to warfarin, 'bridging' concepts are not generally recommended for NOACs.
EVALuna2:15984